Adolescent Pregnancy The Unmet Need for Psychological Research - Hale, Christiane B.; Freese, Margaret P. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
Adolescents contribute nearly 20% of all births in the United States; half of these are unplanned or unwanted. Negative health and socioeconomic consequences are associated with adolescent childbearing, and teenagers account for nearly one-third of all reported therapeutic abortions. Failure to use other than traditional research methods to study antecedents and consequences of teenage pregnancy has resulted in inadequate information for public policy or program development. Age and race comparisons have been made in studies of adolescent sexual behavior; research data point to an increasing number of sexually active adolescents, most of whom do not use contraception regularly or effectively. Studies of social epidemiology of adolescent pregnancies lack quality data from males or couples; reliable data on teenage abortions are also scarce. Productive research by psychologists could be conducted in the areas of developmental issues, antecedents and consequences of adolescent childbearing, and evaluations of programs offering sex education, contraception, abortion, or parenting skills. There is a need for collaborative research efforts by social demographers, epidemiologists, psychologists, and others who could help find viable intervention strategies to reduce unwanted teenage pregnancies. (Author/NRB)
ERIC Note: Paper presented at the Annual Meeting of the Southeastern Psychological Association (26th, Washington, DC, March 26-29, 1980).
Microfiche.
Keywords: Abortions; Adolescents; Birth; Contraception; Intervention; Parenthood Education; Pregnancy; Prevention; Research Needs; Sex Education; Sexuality; Social Planning; State of the Art Reviews; Information Analyses; Speeches/Meeting Papers